MODELING AND SIMULATION OF WELDLINES IN INJECTION MOLDING PROCESS - Mezghani, Khaled (2020)
During the last few decades, considerable developments have been achieved in the area of computer-aided polymer processing, such as: injection molding, thermoforming, and profile extrusion. Injection molding is one of the most important processes of thermoplastic materials. Even though injection molding is simple in principle the real process is quite complex. The complexity of the problem rises from the unsteady and non-isothermal process and the rheological behavior of the molten polymer. The problem is generally solved using numerical techniques and realistic rheological models for quantitative analysis. Usually a good process simulation will predict the final shape of the product and the location of different defects. One of the major defects in the injection molding process is the formation of weldlines that lead to surface imperfections and weak spots in the part. A weldline is a three dimensional region with complex morphology. The location of the weldline is highly dependable on the location of the gates in the mold and the shape of the product. In this paper two different parts with visible weldlines will be compared to the simulation results. The prediction of the weldline location in a relatively complex shape is in good agreement with the real product.